Comparison of Time and Sequence of Permanent Tooth Eruptions in Chinese and Arabic Ethnic Groups - Afif R. Thabrani; Shanty Chairani; Tyas Hestiningsih (Sriwijaya Journal of Dentistry, 2020)
Introduction. Tooth eruption is a process of moving teeth into the oral cavity through the soft tissue and mucosa that lines the jaw until it comes into contact with the antagonistic teeth and functions in mastication. The timing and sequence of tooth eruptions for each individual varies, which is influenced by several factors, one of which is race and ethnicity. Indonesia is known as a multi-ethnic country, including Chinese and Arabic ethnic groups. The purpose of the study was to compare the timing and sequence of eruption of permanent teeth in ethnic Chinese and Arabs.Methods. This type of research is an observational study with a cross-sectional design. The sample of this study was 327 children consisting of 201 Chinese and 126 Arab ethnicities with an age range of 6-13 years. The eruption of all permanent teeth was examined except for the third molar. The mean time to eruption of permanent teeth was calculated using the Karber method. The data were analyzed statistically using the Mann-Whitney test.Results. The first permanent teeth erupted in the two ethnic groups were the mandibular central incisors around the age of 7 years and the last eruption was the maxillary second molar around the age of 11 years. Significant differences in the eruption time of the permanent teeth between ethnicities were shown in the maxillary central and second molars and lateral incisors and mandibular first molars (p <0.05). The eruption sequence pattern in both ethnicities was almost the same except for the canines and second premolars in the upper and lower jaws.Conclusion. There are differences in the timing and sequence of eruption of permanent teeth between ethnic Chinese and Arabs.